Market Survey and Demand Forecasting Studies of Ready-to-Eat Plant-Based Sausage - Mohmad Farid, Nurfarisah Aliyah; Muhammad, Norhayati (Enhanced Knowledge in Sciences and Technology, 2025)
The growing consumer interest in sustainable and healthier food options has fuelled the growth of the plant-based food market. This study investigates the market demand and consumer preferences for ready-to-eat plant-based sausage through a market survey and demand forecasting analysis. There are 385 respondents collected via structured questionnaire, analysed using chi-square test and cross-tabulation. Observation method analysed using thematic analysis to identify patterns in market trend and purchase behaviour. Through questionnaire, the age group of 18-24 years shows highly demand towards this product which is 41.1% and students are recorded the highest demand with 74.3%. Meanwhile through the thematic, the data of observation and recipes are arranged into themes such as main ingredients, pricing, weight and packaging. Attributes such as health benefits, flavourful taste, packaging and affordability were identified as key factors influencing purchasing decision. This study reveals significant in consumer interest with health benefits and flavourful taste as top priorities.